ANALISIS PENDAPATAN PETERNAK PLASMA AYAM PEDAGING (Broiler) POLA KEMITRAAN MODEL CONTRACT FARMING DI KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR (Studi Kasus pada Peternak PT.MITRAANUGRAHSATWA) - Roni Edi Jayanto Sinaga; Cepriadi Cepriadi; Eliza Eliza (Fakultas Pertanian, Universitas Riau, 2016)
The purpose of this research was to analyze the revenue of broiler breeders a pattern partnership contract farmingmodel in plasma breeders of PT. Mitra Anugrah Satwa (MAS) which is in Kampar Kiri Tengah District Kampar Regency. The method used in this research is a survey method. The Samples in this research using random sampling. The number of respondents is 5people. The results of this research showed that the average income of the breeders and the efficiency of on-farm business in plasma breeders PT. Mitra Anugrah Satwais profitable and feasible to be developed, it is seen from the acquisition value of R/C R ≥ 1. The mean earningplasma breeders of PT. Mitra Anugrah Satwaisequal to Rp.14.415.224,64/period with acquirement of mean of R/CRis 1.09.